2009
DOI: 10.1111/j.1468-1293.2009.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Deferred modification of antiretroviral regimen following documented treatment failure in Asia: results from the TREAT Asia HIV Observational Database (TAHOD)

Abstract: Objective The aim of the study was to examine the rates and predictors of treatment modification following combination antiretroviral therapy (cART) failure in Asian patients with HIV enrolled in the TREAT Asia HIV Observational Database (TAHOD). Methods Treatment failure (immunological, virological and clinical) was defined by World Health Organization criteria. Countries were categorized as high or low income by World Bank criteria. Results Among 2446 patients who initiated cART, 447 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In this study, we identified a large number of individuals with confirmed virologic failure in routine clinical practice, followed for a median of 4.3 years after ART initiation (2.2 years after confirmed failure). We found that switching to second-line protease inhibitor based therapy was delayed in many patients, a practice that others have found to be common, even in settings in which routine HIV RNA monitoring and second-line therapy are available [3235]. We found, after adjustment for measured confounders, that remaining on first-line therapy following confirmed virologic failure significantly increased mortality.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, we identified a large number of individuals with confirmed virologic failure in routine clinical practice, followed for a median of 4.3 years after ART initiation (2.2 years after confirmed failure). We found that switching to second-line protease inhibitor based therapy was delayed in many patients, a practice that others have found to be common, even in settings in which routine HIV RNA monitoring and second-line therapy are available [3235]. We found, after adjustment for measured confounders, that remaining on first-line therapy following confirmed virologic failure significantly increased mortality.…”
Section: Discussionmentioning
confidence: 65%
“…In Khayelitsha HIV cohort, 84% remained virologically suppressed at 5 years [53 ]. Similarly high success rates have been reported in diverse settings [55,57,[59][60][61][62][63], summarized in Table 1 [21 ,52,53 ,54 ,55,56,58-62,79]. Thus, the responses to cART in LMICs, in terms of CD4 þ cell count and viral load, can be robust, sustained and comparable to those seen in high-income settings, at least in first 4-5 years of follow-up [19,22,57].…”
Section: Othersmentioning
confidence: 75%
“…The situation is compounded by the fact that a majority of treatment programs either do not provide viral load monitoring or wait to commence second-line treatment till viral load increases to 1000-10 000 copies/m [85 ], there by delaying necessary switch in treatment till immunological or clinical failure occurs and increasing the risk of future failures. In TAHOD cohort, over 50% patients who failed continued the failing regimen [63], demonstrating how second-line options remain elusive to many failing patients in LMICs. More recently, WHO recommended universal availability of third-line options [67].…”
Section: Access To Second-line Treatment and Beyondmentioning
confidence: 98%
“…34 Similarly, in Asia, treatment modification after confirmed failure is frequently subject to delay. 35 In a study of 16,591 patients starting ART in sub-Saharan Africa, cumulative mortality at 1 year was 2.2% in patients on a non-failing first-line regimen, 4.2% in patients who switched from a failing first-line regimen to a second-line regimen, and 11.7% in those who remained on a failing first-line regimen (p<0.0001). 20 Although patients that experienced a delay in second-line initiation in our analysis did not fare worse than those switched within 6 months of first-line failure, we did observe a significant association between high viral load at switch and treatment failure.…”
Section: Discussionmentioning
confidence: 99%